Harmonized aerosol size distribution, cloud condensation nuclei, chemistry and optical properties at 10 sites - Elisabeth Andrews; Inés Zabala; Gerardo Carrillo-Cardenas; Gloria Titos; Juan Andrés Casquero-Vera; A. Gannet Hallar (Scientific Data)
Abstract A harmonized data set of aerosol particle number size distributions and cloud condensation nuclei (CCN) concentrations at 10 US Department of Energy (DOE) Atmospheric Radiation Measurement (ARM) sites is presented. Additional complementary data including total particle number concentration, aerosol chemical composition and aerosol optical properties are included where available. Calculated parameters related to particle activation, (e.g., activated fraction, hygroscopicity parameter and critical diameter) are provided. DOE/ARM data are acquired and processed following DOE/ARM protocols which are based on international recommendations. Here, the data have undergone additional stages of quality assessment including various closure tests. This data set may be useful for studying aerosol processes and, with other data, assessing aerosol-cloud- interactions. High-resolution (5-min) data is provided along with 1-h averaged data, making the data set suitable for exploring the importance of new particle formation (NPF) events on CCN concentrations. Further applications include model and satellite evaluation of aerosol size distributions and CCN concentrations, and exploring relationships among different aerosol properties which may be useful for improving model parametrizations.